Perancangan Aplikasi Chatbot Sebagai Media E-Learning Bagi Siswa - Muhammad Alifyan Zulkarnain; Muhammad Fajri Raharjo; Meylanie Olivya (Teknik Elektro Politeknik Negeri Padang, 2020)
The conventional question and answer method has limited time, space and level of understanding from each student so that it becomes an obstacle to the ineffective teaching and learning process. Global pandemic events that have a negative impact on the education sector. So that the teaching and learning process is temporarily stopped at school and diverted online. This study aims to produce a chatbot application as a media for distance learning that helps the teaching and learning process of teachers and students . In practice, This research uses telegram as a chatbot media. The method used for data collection is by interview, literature study, and observation. Testing will be carried out with a black box, calculation of accuracy, and a user acceptance test in the form of distributing questionnaires. The results of this study produce a Chatbot Application as an E-Learning Media for Students that can help teachers in providing distance learning to students efficiently and easily.